Capital structure, equity mispricing, and stock repurchases - Bonaimé, Alice Adams; Öztekin, Özde; Warr, Richard S. (Journal of Corporate Finance, 2014)
We evaluate motives for share repurchases using a unified framework where a firm has a target capital structure and has equity that can be mispriced. We document that capital structure adjustments are a value-increasing motive for repurchases and that the extent to which adjusting capital structure through a repurchase creates value depends on the undervaluation of the firm. Underlevered and undervalued firms enjoy the greatest economic gains from a repurchase, as evidenced by the stock price reaction to the repurchase announcement, and these firms are more likely to announce a share repurchase program.